Extraordinary Circumstances : The Seven Days Battles - Burton, Brian K., 1959- (Book collections on Project MUSE., 2001)
The Seven Days Battles was the first campaign in the Civil War in which Robert E. Lee led the Army of Northern Virginia and has been the subject of a number of fine historical treatments. None, however, is more detailed and engaging than Burton's closely observed account. It is a moment-by-moment story of the campaign that lifted Southern spirits, began Lee's ascent to fame, and almost prompted European recognition of the Confederacy.